Socio-Demographic Factors Contributing to Teenage Pregnancy in Bidibidi Refugee Settlement Zone Four Yumbe District. - Momone, Evaline (Kabale University, 2024)
The study aimed to explore the socio-demographic factors contributing to teenage pregnancy in the Bidibidi Refugee Settlement, Zone Four, Yumbe District. Objectives guided the study, were: to investigate the socio-demographic characteristics that are associated with the occurrence of teenage pregnancy among girls to assess the impact of displacement in the refugee context on the prevalence of teenage pregnancy among girls in the Bidibidi Refugee Settlement, and to develop practical recommendations for tailored interventions aimed at addressing the unique challenges faced by teenage girls in the Bidibidi Refugee Settlement. The researcher adopted both qualitative and quantitative data from 90 respondents. Data collection was done using questionnaires, and an interview guide and analysis were done. Some respondents showed that lower levels of education are often linked to higher rates of teenage pregnancy. Some respondents showed that poverty and limited economic opportunities increase the likelihood of teenage pregnancies. Respondents gave their opinions that forced displacement often disrupts the education of refugee girls. Some respondents showed that refugees face challenges in accessing adequate healthcare, including reproductive health services. Also from the questionnaire, respondents mentioned that displacement often leads to economic instability, with refugees facing difficulties in securing employment and meeting basic needs. Respondents revealed that implementing age-appropriate and culturally sensitive sex education programs that cover topics such as reproductive health, contraception, consent, and healthy relationships. The study concluded that the occurrence of teenage pregnancy is a multifaceted issue influenced by various socio-demographic factors. Understanding and addressing these factors is crucial for implementing effective preventive measures and support systems. The socio-demographic factors contributing to teenage pregnancy include age, socioeconomic status, education, family structure, cultural and religious influences, access to healthcare, peer influence, geographical location, and media impact. The study recommends that there is a need to implement age-appropriate and culturally sensitive sex education programs in schools to provide adolescents with accurate information about reproductive health, contraception, and healthy relationships. There is also a need to ensure affordable and accessible reproductive healthcare services, including family planning and contraceptives, to empower teenagers to make informed choices about their reproductive health.